Problems of Electronic Mortgage Implementation for the Banking Activities - Mukhidin Mukhidin; Achmad Irwan Hamzani (Faculty of Law, Universitas Jenderal Soedirman, 2022)
Banking credit is a basic need for the community, especially business actors. In the development of Mortgage Rights in Indonesia, the Government provides services including electronically integrated Registration of Mortgage Rights based on the Regulation of the Head of the National Land Agency No. 9 of 2019 and ATR/BPN Ministerial Regulation No. 5 of 2020 concerning Electronic Mortgage Services and / or hereinafter referred to as